Kekerasan Verbal dalam Interaksi Digital: Analisis Wacana Konten Program MBG pada Akun Instagram @mastercobuzier - Rada Lailatul Chusna; Roziana Febrianita (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines the practices of verbal and non-verbal violence found in Instagram reels contentby @mastercobuzier in response to public criticism of the (MBG) Program. Using Rodney H. Jones’s digital discourse analysis approach, this research explores how violence is produced and normalized through text, context, interactional actions, and power relations. The findings reveal forms of verbal violence such as the utterances “pala lu PA!”, “gue tabok!”, and “sekaya apa ente?”, which function as symbolic intimidation. Non-verbal elements including heightened intonation, pointing gestures, and emojis amplify the aggression and shape audience reception. The content shifts policy criticism into moral judgment of individuals, constructing the student who voiced criticism as improper and illegitimate. Ideologically, this pattern demonstrates elitist populism, in which public figures employ moral authority to silence criticism. Audience responses reveal the reproduction of symbolic violence through sarcastic comments, emphasizing that these power dynamics are not merely local phenomena but reflect global patterns in how public figures and digital platforms shape aggressive communication norms across cultures.